TEORI PERUBAHAN SOSIAL DALAM MEMAHAMI HADIS KEPEMIMPINAN PEREMPUAN - Afrizal Fahmi Ali (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2022)
This article aims to find out how to understand women's leadership by using a sociological approach in this case the theory of social change. Because the hadith cannot be separated from the background of the emergence of hadith (ashbāb al-wurūd) and the social life of each place and time can be different and can change. In this case, the study used is qualitative and literature, and the method used is descriptive analysis, first describing the text about women's leadership, then describing the analysis using a social change theory approach. The result of the explanation obtained is that the social changes that occur make women the same opportunities as men in various fields such as politics and leadership. And female leaders have a leadership style that is lacking in men (and vice versa) which makes them complementary.